Building Young Generation Character: Strategies for Internalizing The Disciplinary Character of Junior High School Students - Etty Ratnawati; Nasehudin Nasehudin (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2024)
The purpose of this study is to examine various strategies for internalizing the disciplinary character of junior high school students applied by schools and teachers in order to create effective learning in the classroom. This is based on violations committed by students, even though school rules have been applied. Through the instillation of discipline in students, it is hoped that self-awareness will emerge to comply with applicable rules/norms, not because of a sense of compulsion to obey applicable rules/norms.Â  This type ofresearch is descriptive qualitative research, where the data collected are data from observations in the field, and interviews with principals, curriculum wakasek, student affairs, teachers, and students, as well as from literature that supports the concept of internalization of disciplinary character. The data validity technique used is a triangulation technique. Data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions and verification. The results showed that there are three approaches in internalizing the disciplinary character of students in SMP Negeri 3 Sumber, namely the school culture approach, Classroom Management/Climate, and social-emotional development through extracurricular activities and social care movements. As for the implementation of the strategy of internalizing the character of student discipline, there are no violations that exceed reasonable limits such as drugs and others, but they have not been 100% successful, there are still those who violate school rules. The obstacles that cause it are lack of cooperation between parents and the school, social and conformity factors, difficult transportation, and mediocre family economy.Keywords: strategy, internalization, disciplined character.